THE EFFECT OF ROLE AMBIGUITY, ROLE CONFLICT, EXTERNAL LOCUS OF CONTROL, AND NEUROTICISM ON JOB STRESS - WIBOWO, PUSPA SAKTI HARUM; PURNOMO, RATNO (INDONESIAN RESEARCH SOCIETY, 2019)
The purpose of this study was to analyze the effect of role ambiguity, role conflict, external locus of control, and neuroticism on job stress. The research methodology used for this study is a quantitative approach. The population in this study were 165 people with 120 people who became respondents. The analysis technique used is multiple regression analysis. The sampling technique in this study was a random sampling technique. The software used to analyze the data is SPSS 18. The results showed that role ambiguity, role conflict, external locus of control, and neuroticism had an effect on job stress. The implications in this study indicate that job stress is influenced by stressors from organizations and individuals, so that every organization and individual is expected to be able to control work stress.